Efficiency of R&D spending at the US Universities. (November 2019) - Bogomolova, Arina; Balk, Igor; Semenov, Evgeniy; Ivashchenko, Natalya; Temkin, Anatoly
Abstract: This article focuses on the efficiency of using university R&D funding. As a parameter of efficiency, we took the so-called "article cost" - the amount of money received for research in the previous year to get 1 article in the current year. It turned out that the average cost of an article at an American university is $101 thousand over the past 8 years. After analyzing a set of universities, it became obvious that the article cost is stable for each university over time, respectively, there are some non-random parameters that affect this value. We have also identified several parameters that, logically, can influence the university performance indicator. They are coefficient of specialization, number of students, number of staff and student per staff ratio, number of articles and others. We also examined several other parameters and made a statistical review of a typical U.S. university with a large research budget. At the end of the article, there is a least squares model that, using these parameters, explains more than half of the differentiation of the efficiency parameter.